Fusion Surgery Required for Recurrent Pediatric Atlantoaxial Rotatory Fixation after Failure of Temporary Fixation with Instrumentation - Yoshiyuki Matsuyama; Tetsuhiro Ishikawa; Ei Ozone; Masaaki Aramomi; Seiji Ohtori (Case Reports in Orthopedics)
In cases of chronic irreducible and recurrent unstable atlantoaxial rotatory fixation (AARF), closed reduction and its maintenance are often unsuccessful, requiring surgical treatment. The purpose of the present report is to describe a rare case of pediatric AARF that required multiple treatments. A 6-year-old boy was diagnosed as having type 2 AARF. After conservative treatment, the patient was treated with temporary fixation surgery (C1-C2 Magerl) without a bone graft in consideration of motion preservation after screw removal. AARF recurred after the screw removal and required fusion surgery (Magerl–Brooks) with an iliac bone graft. Ultimately, bone union was achieved and the screws were removed 11 months after the surgery. We recommend surgeons be cautious when choosing temporary fixation surgery for AARF in small children. Further investigation is needed to determine the optimal time before screw removal.